Evaluating The Efficiency of a Facility Through a Detailed Energy Audit - Kapan, Sinan (Bitlis Eren Üniversitesi, 2026)
Global climate change, triggered by rising greenhouse gas emissions, continues to threaten our planet. One of the most effective ways to reduce greenhouse gas emissions is through energy efficiency practices in industrial facilities. According to the Energy Efficiency Law enacted in Türkiye, factories with an energy capacity exceeding 1,000 Tonne of oil equivalent (TOE) are required to undergo an energy audit every four years. This study, based on the data gathered from a detailed energy audit conducted at a manufacturing facility, proposed energy efficiency projects. Six areas with energy savings potential were identified. These projects include the installation of an energy monitoring and automation system in the facility, elimination of compressed air leakage, lighting conversion, insulation, solar power plant installation, and replacing inefficient pump motors with more efficient motors. Implementation of the proposed projects will result in annual savings of $64,476.5, equivalent to the monetary equivalent of 90.06 TOE of energy. Environmental impact analysis revealed a reduction in greenhouse gas emissions of 418 tons. The total initial investment cost of the 6 proposed projects is $238,060.6, and the average payback period is calculated as 3.7 years.
Keywords: Energy Efficiency; Enerji Verimliliği